Gender Diversity as a Moderator: Exploring its Impact on the Link Between Sustainability Reporting and Firm Value - Chen, Ming; Robiani, Bernadette; Saftiana, Yulia; Mukhtaruddin, Mukhtaruddin (Journal of International Conference Proceedings, 2024)
This study seeks to examine the influence of gender diversity on the relationship between sustainability reporting and firm value in Indonesian manufacturing enterprises from 2021 to 2023. This study utilizes secondary data derived from the annual reports of firms listed on the Indonesia Stock Exchange (IDX). This study measures gender diversity by the percentage of female members on a company's board of commissioners. Sustainability reporting is measured using the GRI 2016 standards, with the economic sector divided into 6 subsections consisting of 13 indicators, the environmental sector divided into 8 subsections consisting of 30 indicators, and the social sector divided into 19 subsections consisting of 34 indicators. Firm value is measured using the Price-to-Book Value ratio. The research sample consists of consumer non-cyclicals, and purposive sampling technique is employed. To analyze the data, this study applies Moderated Regression Analysis (MRA) with the assistance of SPSS. The results of the study indicate that gender diversity does not moderate the effect of sustainability reporting on firm value. This finding suggests that while sustainability reporting may influence firm value, gender diversity does not have a significant moderating effect in the context of manufacturing companies in Indonesia. This study recommends considering other factors that may be more effective in moderating the relationship between sustainability reporting and firm value.Keywords: "Gender Diversity"; "Sustainability Report"; and "Firm Value"